KUALITAS LABA DAN PENGUNGKAPAN SUKARELA DAMPAKNYA TERHADAP BIAYA MODAL EKUITAS MELALUI ASIMETRI INFORMASI - Ibnu Abni Lahaya (University of Merdeka Malang, 2017)
This study aimed to examine the effect of earning quality and voluntary disclosure on cost ofequity capital with information asymmetry as an intervening variable. The study was conductedby analyzing 118 manufacturing companies listed in Indonesia Stock Exchange during the years2013 to 2015 by using path analysis. The results of this study indicate that information asymmetrymediating the relationship of earnings quality and voluntary disclosure on cost of equitycapital. These findings indicate that the company may affect the cost of equity capital by minimizethe degree of information asymmetry with improving earning quality and expanding voluntarydisclosure.The reduced cost of equity capital caused by low rate of return required by investorsbecause the information presented to minimize the level of information asymmetry. This studyindicates that information has an important role to lowering information asymmetry and cost ofequity capital, as indicated by the response of investors and other market participants to theinformation disclosed by company.